2014
DOI: 10.1002/ajmg.a.36433
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel missense mutation of MAF in a Japanese family with congenital cataract by whole exome sequencing: A clinical report and review of literature

Abstract: Congenital cataracts are the most important cause of severe visual impairment in infants. Genetic factors contribute to the disease development and 29 genes are known to cause congenital cataracts. Identifying the genetic cause of congenital cataracts can be difficult because of genetic heterogeneity. V-maf avian musculoaponeurotic fibrosarcoma oncogene homolog (MAF) encodes a basic region/leucine zipper transcription factor that plays a key role as a regulator of embryonic lens fiber cell development. MAF mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 18 publications
5
28
0
Order By: Relevance
“…B). Up until this report, five mutations have been found in the basic region of MAF , in patients with isolated ocular abnormalities, all clustered around the b‐zipper domain [Jamieson et al., , ; Vanita et al., ; Hansen et al., ; Narumi et al., ] (Fig. B).…”
Section: Discussionmentioning
confidence: 99%
“…B). Up until this report, five mutations have been found in the basic region of MAF , in patients with isolated ocular abnormalities, all clustered around the b‐zipper domain [Jamieson et al., , ; Vanita et al., ; Hansen et al., ; Narumi et al., ] (Fig. B).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a variant in the DNA-binding domain of MAF (p.(Arg288Pro)) in a three generations family with lamellar cortical and nuclear pulverulent cataract, microcornea, and iris coloboma. Narumi et al [32] identified a MAF variant (p.(Gln303Leu)) through whole exome sequencing in a family with phenotypically variable congenital cataract (lamellar or anterior polar with microcornea and iris coloboma). The affected proband was diagnosed with lamellar cataract without any other eye malformation with language development delay and autism.…”
Section: Discussionmentioning
confidence: 99%
“…The development of molecular genetics and technology has facilitated extensive investigations into the familial pedigree of congenital cataract via the use of new sequencing technologies such as whole genome sequencing and WES (Narumi et al, 2014). Consequently, this allows us to elucidate the pathogenesis of sex-linked congenital cataract at a molecular level and study the gene-gene and gene-environment interactions, which in turn could help provide comprehensive patient services.…”
Section: Discussionmentioning
confidence: 99%